Consolidation and generalization of theoretical knowledge through independent education (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Strengthening and generalization of students' theoretical knowledge of science through independent education and formation of students' skills and abilities to independently learn the basics of science; development of students' cognitive activity, independent creative work skills and creative skills; is to determine the skills of self-professional development and improvement in students.